The Clinicopathological Features and Prognostic Significance of HER2-Low in Early Breast Tumors Patients Prognostic Comparison of HER-Low and HER2-Negative Breast Cancer Stratified by Hormone Receptor Status - Sanaa Gamrani; Laila Akhouayri; Sara Boukansa; Mehdi Karkouri; Hinde El Fatemi (The Breast Journal)
Introduction. There has been increased interest in HER2-low breast tumors recently, as these tumors may have distinct clinical and molecular characteristics compared to HER2-negative and HER2-positive tumors. A new nomenclature has been proposed for HER2 1+ and HER2 2+ tumors that are confirmed negative according to fluorescence in situ hybridization (FISH). These tumors are now referred to as HER2-low, and it is thought that they may represent a distinct subtype of breast cancer that warrants further investigation. In this study, we aimed to evaluate the clinicopathological characteristics and prognostic impact of this particular subtype in a North-African context where HER2-low breast cancer is a relatively understudied subtype, particularly in non-Western populations. Methods. We conducted a retrospective cohort study on 1955 breast tumors in Moroccan patients over 10 years, collected at the Pathology Department of Ibn Rochd University Hospital in Casablanca and at the pathology department of Hassan II University Hospital in Fes. We elaborated on their complete immunohistochemical profile based on the main breast cancer biomarkers: Ki-67, HER2, estrogen, and progesterone receptors. Their overall survival and disease free survival data were also retrieved from their respective records. Results. Out of 1955 BC patients, 49.3% were classified as HER2-low; of which 80.7% and 19.2% were hormone receptors positive and negative, respectively. The clinicopathologic features indicate that HER2-low subtype tumors behave much more like HER2-positive than HER2-negative tumors. The survival analysis showed that the HER2-low subtype-belonging patients present significantly the poorest prognosis in disease-free survival (p=0.003) in comparison with HER2-negative ones. When considering the hormonal status, hormonal-dependent tumors show a significant difference according to HER2 subtypes in disease-free survival (p<0.001). Yet no significant difference was shown among hormonal negative tumors. Moreover, patients with hormonal positive tumors and simultaneously belonging to the HER2-low subgroup present a significantly good prognosis in overall survival compared to the ones with hormonal negative tumors (p=0.008). Conclusion. Our study has shown that the HER2-low phenotype is common among hormone-positive patients. The clinicopathological features and prognostic data indicate that the hormonal receptors effect and HER2 heterogeneity are crucial factors to consider. It is important to note that this particular subgroup is different from the HER2-negative one and should not be treated in the same way. Therefore, this study offers a new perspective in the management of HER2-low patients and can serve as a basis for future prospective analyses.